2020
DOI: 10.3390/foods9091281
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Bioactivities of Polyphenols Eco Extracts from Coffee Grounds after In Vitro Digestion

Abstract: Coffee grounds are a valuable source of bioactive compounds. In Romania, most of the amount obtained is lost through non-recovery; the rest is occasionally used as organic fertilizer. The coffee grounds were selected according to the roasting degree: blonde roasted (BR), medium roasted (MR), and dark roasted (DR). The study aimed to evaluate three extracts, obtained with a mixture of ethanol/water/acetic acid (50/49.5/0.5), depending on the roasting degree. The majority phenolic component, the antioxidant, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…The focus on chlorogenic acid is due to its potential health bene ts described in previous studies, including free radical scavenging capacity, antiin ammatory, antidiabetic, and anticancer effects 20 . Cinnamic acid, which is predominant in the present study in agreement with Vamanu et al 21 , has generally been reported to be phenolic constituents in SCG in previous research but in much lower concentrations with respect to the extraction technique 22 . As explained above, the variations might be due to many reasons, including solvent, solvent/sample ratio, extraction time, extraction method, and temperature.…”
Section: Resultssupporting
confidence: 93%
“…The focus on chlorogenic acid is due to its potential health bene ts described in previous studies, including free radical scavenging capacity, antiin ammatory, antidiabetic, and anticancer effects 20 . Cinnamic acid, which is predominant in the present study in agreement with Vamanu et al 21 , has generally been reported to be phenolic constituents in SCG in previous research but in much lower concentrations with respect to the extraction technique 22 . As explained above, the variations might be due to many reasons, including solvent, solvent/sample ratio, extraction time, extraction method, and temperature.…”
Section: Resultssupporting
confidence: 93%
“…The differences were assessed by analysis of variance (ANOVA) followed by a Tukey post-hoc analysis. The experimental data analysis and correlation were performed using the IBM SPSS Statistics software package (IBM Corporation, Armonk, NY, USA) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The standard and sample solutions were diluted in methanol. The identification of the compounds was realized by the addition of standards, and the retention times were compared at λ = 280 nm [8]. The linearity of the response was established for each polyphenol by building the calibration curves.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…Banana peels extract has such use in reducing oxidative stress, a major cause of many chronic diseases [7]. In direct relation with the characterization of the biological effect and the phytochemical profile [8], will determine the procurement of competitive products that help increase the products' efficacy [9]. That may include biopharmaceutical compounds integrated into the cosmetic products [10].…”
Section: Introductionmentioning
confidence: 99%